Augmented Reality Perakitan Komputer - Deo Febrino Mudri; H.A Mooduto; Rita Afyenni (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
With the development of Augmented Reality (AR) technology, life becomes more real, by combining the virtual world into the real world in 3-dimensional form using the camera feature. The purpose of this application is to assist in the teaching and learning process in computer assembly subjects by utilizing augmented reality technology. AR is very helpful in visualizing the shape of objects, so the creation of this application as a learning media for components in computer assembly helps in accessing information and interacting using 3-dimensional objects. The method used is Marker Based Tracking, so to display the object a marker is needed. This application can observe from various sides so that it is even more real. It is hoped that this application will provide benefits to users in introducing and providing information about computer assembly learning using augmented reality technology.